Experimental study on the effect of sound stimulation on hearing and behavior of juvenile black rockfish (Sebastes schlegelii) - Wang, Yining; Huang, Liuyi; Xing, Binbin (Frontiers in Marine Science, 2023)
Assessing the potential impacts of wind farm noise on fish is a crucial aspect of Environmental Impact Assessment (EIA) studies. There is increasing evidence of disturbances and effects on hearing and behavior in animals. The black rockfish (Sebastes schlegelii) is a commercially valuable rocky reef fish native to East Asia. However, empirical studies that measure the actual consequences are lacking. In this study, we used auditory evoked potentials (AEP) to assess the effects of dominant frequency noise emitted by offshore wind farms on the auditory sensitivity, hearing threshold, swimming, and feeding behavior of juvenile black rockfish. The experimental findings revealed that the most sensitive sound frequency was 200 Hz, with the lowest hearing threshold recorded at 86.4 ± 3.4 dB re 1 μPa. Following 3 and 7 days of exposure to 200 Hz noise at 110 dB, threshold shifts in black rockfish reached 19.0 dB and 13.3 dB, respectively. During the subsequent recovery phase, these shifts decreased to approximately 9.8 dB after 3 days, respectively. The noise-exposed group exhibited higher swimming duration, moving distance, and caudal fin swing frequency compared to the control group without noise exposure. Furthermore, noise prolonged the feeding rate of black rockfish. Our findings provide the first evidence of noise-induced temporary threshold shift and behavioral disturbances in juvenile black rockfish, implying potential fitness consequences associated with noise pollutant.